Comparison of two invasive non-surgical treatment options for uterine myomas: uterine artery embolization and magnetic resonance guided high intensity focused ultrasound-systematic review - Madina Yerezhepbayeva; Milan Terzic; Gulzhanat Aimagambetova; Byron Crape (BMC, 2022)
Abstract Background Uterine Artery Embolization (UAE) and Magnetic Resonance guided High Intensity Focused Ultrasound (MRgHIFU) are two noninvasive treatments for uterine leiomyoma. Methods This systematic review, following PRISMA guidelines, analyzed the effectiveness of two treatments by comparing percent fibroid volume shrinkage immediately after the procedure and after 3, 6, 12 and 24 months of follow-up and also assessed and compared common complications following treatment. The search utilized Science Direct, PubMed, MEDLINE, Google Scholar and BioMed Central databases, selecting manuscripts published during the period 2000 and 2020. Studies with premenopausal patients with previous treatments for uterine leiomyoma and/or with other pelvic diseases were excluded. Results Twenty-nine papers satisfied inclusion and exclusion criteria. Results were pooled and stratified by treatment and follow-up time. Weighted fibroid volume percent shrinkage after UAE was statistically significantly greater than MRgHIFU at 6, 12, and 24 months follow-up times. However, UAE had statistically significantly more complications, such as pain, nausea and vomiting. However, this study cannot conclude that UAE is more effective than MRgHIFU due to confounding factors.